2022
DOI: 10.5194/acp-22-11543-2022
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric oxidation mechanism and kinetics of indole initiated by ●OH and ●Cl: a computational study

Abstract: Abstract. The atmospheric chemistry of organic nitrogen compounds (ONCs) is of great importance for understanding the formation of carcinogenic nitrosamines, and ONC oxidation products might influence atmospheric aerosol particle formation and growth. Indole is a polyfunctional heterocyclic secondary amine with a global emission quantity almost equivalent to that of trimethylamine, the amine with the highest atmospheric emission. However, the atmospheric chemistry of indole remains unclear. Herein, the reactio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…121 However, Xue et al found that ˙OH addition was the dominant pathway for the reaction of ˙OH with indole which is a polyfunctional heterocyclic secondary amine. 122…”
Section: Oxidation Kinetics and Mechanisms Of Atmospheric Aminesmentioning
confidence: 99%
See 4 more Smart Citations
“…121 However, Xue et al found that ˙OH addition was the dominant pathway for the reaction of ˙OH with indole which is a polyfunctional heterocyclic secondary amine. 122…”
Section: Oxidation Kinetics and Mechanisms Of Atmospheric Aminesmentioning
confidence: 99%
“…Recently, Xue et al also found that both ˙Cl addition and hydrogen-abstraction from N-sites were feasible for the reaction of indole with ˙Cl, while ˙OH addition was the dominant pathway in the case of the ˙OH reaction. 122 Obviously, the reaction of ˙Cl with amines is quite different from that of ˙OH. Hence, to assess the fate of atmospheric amines more accurately, it is necessary to consider both the atmospheric concentrations of ˙Cl and ˙OH and their initial reaction steps with atmospheric amines.…”
Section: Oxidation Kinetics and Mechanisms Of Atmospheric Aminesmentioning
confidence: 99%
See 3 more Smart Citations